2021
DOI: 10.3390/axioms10030164
|View full text |Cite
|
Sign up to set email alerts
|

Rough Approximation Operators on a Complete Orthomodular Lattice

Abstract: This paper studies rough approximation via join and meet on a complete orthomodular lattice. Different from Boolean algebra, the distributive law of join over meet does not hold in orthomodular lattices. Some properties of rough approximation rely on the distributive law. Furthermore, we study the relationship among the distributive law, rough approximation and orthomodular lattice-valued relation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Step 2: Calculating the gray scale fitness value of each particle according to the Equation (20). If it is better than the individual extreme value of the current position of the particle, set pbest to the position of the particle, record the position of the particle and update the global extreme value.…”
Section: Image Segmentation Algorithm Based On Psomentioning
confidence: 99%
See 1 more Smart Citation
“…Step 2: Calculating the gray scale fitness value of each particle according to the Equation (20). If it is better than the individual extreme value of the current position of the particle, set pbest to the position of the particle, record the position of the particle and update the global extreme value.…”
Section: Image Segmentation Algorithm Based On Psomentioning
confidence: 99%
“…Rough set was first proposed by Polish professor Z. Pawlak in 1982. It is another mathematical method for processing uncertain information after probability theory and fuzzy set theory [20,21]. As a mathematical tool for describing uncertainty, it can effectually analyze and process incomplete information such as inconsistency, inaccuracy and incompleteness, it can find hidden knowledge and reveal potential laws [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Pawlak formed rough sets by assigning objects related to the confirmation of ideas that fell within the boundary line region, which is defined as the difference set between the upper and lower approximation sets [10][11][12]. Because rough sets can be described by explicit mathematical formulas, the number of fuzzy set elements can be calculated (i.e., the fuzziness between 0 and 1 can be determined through calculation) [10][11][12]. This feature offers an effective means of dealing with the routine nature of unclear problems and managing uncertainty with incomplete information or knowledge.…”
Section: Rough Set Theorymentioning
confidence: 99%
“…In addition, the study also used rough set theory to discover the weighting of the attributes affecting students' final scores. Rough set theory, proposed by Pawlak, has advantage of being able to obtain the same knowledge as the original decision-making system without losing any information, and without obeying any assumptions [10][11][12]. The main purpose of rough set theory is to extract rules from an information system composed of an object and its corresponding attribute factors that are sufficient to describe under which attribute conditions an object should be classified [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Hassan [25] showed that rough set model with quantum logic can be used for recognition and classification systems. In our previous work [26,27], we proposed a rough set model based on quantum logic. We defined rough approximation operators via join and meet on a complete orthomodular lattice (COL).…”
Section: Introductionmentioning
confidence: 99%